Hospital Management Information System Audit Based On COBT 4.1 in Jemursari Islamic Hospital Surabaya - Yudha, Bayu Okta Anggara; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Some IT policies does not fully implemented yet in the entire department at RSI Jemursari regarding the application of Sistem Informasi Manajemen Rumah Sakit for it business purposes. As a result, the data in each department are not in sync and irrelevant with the IT policies. The problems still remain at RSI Jemursari likewise the unclear cause to date. RSI Jemursari used COBIT 4.1 standard and under the scope of Internal Business Processes perspective according to the Balance Scorecard when performing information system audit to resolve the problems. ISACA stage is chosen in performing information system audit consists of four phases which are planning, preparing, performing, and audit reporting. The management information system audit result reach 3.51 ending level value reach which included in defined category that also means the procedure have been standardized and documented, be communicated through adequate training and obligated to implement the standard and deviation. Some procedures are well-executed but it just a matter of formalization for the daily tasks. The entire IT procedures and policies are still lacking or undocumented yet. This research delivers the improvements for the hospital management information system process.